High capacity and high stability lithium-ion battery using nano Sn/SnS-decorated carbon leaf anode and LiCoO2 cathode for consumer electronics. (1st April 2020) - Duraisamy, E.; Archana, S.; Prasath, A.; Elumalai, P.
Abstract: Nano tin or tin sulfide-decorated nitrogen-doped carbon leaves (Sn-NCL or SnS-NCL) were prepared by conventional pyrolysis of [Sn(salen)] complex followed by hydrothermal treatment. Material characterizations confirmed the formation of Sn-NCL or SnS-NCL with the leaf-like morphology. The electrochemical characterizations performed on the CR 2032-type coin cell consisting of the SnS-NCL anode delivered stable discharge capacity of 600 mA h g −1 for long cycle. The synergistic contributions involving conversion/re-conversion and alloying/de-alloying reactions with lithium seemed to such an excellent full cell capacity. The carbon matrix provided cushion to tolerate the volume expansion and facilitated Li + ion/electron transports in the anode electrode. Consequently, the fabricated CR-2032 type full cell consisting of the SnS-NCL anode and the LiCoO2 cathode delivered stable discharge capacity over 400 mA h g −1 at 0.2C-rate with excellent rate capability and cycling stability. Graphical abstract: Image 1003575 Highlights: Sn/SnS-NCL was generated by pyrolysis of [Sn(salen)] complex followed by hydrothermal treatment. The leaf-like morphology for the Sn/SnS-NCL composite has been observed. For the first time, high capacity of 400 mA h g −1 has been observed for the lithium full cell with excellent rate capability and cycling stability. The synergistic contributions of conversion/re-conversion and alloying/de-alloying reactions resulted in such an excellent performance. The carbon leaves acted as cushion to accommodate the volume expansion during lithiation.